Correction: Irvine et al. Transpersonal Ecodelia: Surveying Psychedelically Induced Biophilia. Psychoactives 2023, 2, 174–193 - Alexander Irvine; David Luke; Freya Harrild; Sam Gandy; Rosalind Watts (Psychoactives)
The authors would like to make the following corrections to this published paper [...]